The development of social learning: from pedagogical cues to selective learning - Ishikawa, Mitsuhiko; Itakura, Shoji (Frontiers in Psychology, 2024)
Learning new information from others, called social learning, is one of the most fundamental types of learning from infancy. Developmental studies show that infants likely engage in social learning situations selectively and that social learning facilitates infant information processing. In this paper, we summarise how social learning functions support human learning from infancy focusing on two aspects of social learning; pedagogical learning and selective learning. We also provide an overview of the developmental process of social learning based on the findings of developmental research. This review suggests that the learning facilitation effects of pedagogical learning decrease with development, while the facilitation effects of selective learning are observed even in older ages. The differences in these learning facilitation effects are considered to be due to the differences in the utility of learning in uncertain environments. The findings of the studies imply the unique nature of human social learning and the critical role of social interactions in cognitive development. Understanding the development of social learning provides valuable insights into how infants learn and adapt in complex social environments